Pemberdayaan Guru Sekolah Dasar Melalui Pelatihan Koding dan Kecerdasan Artifisial di Kota Bengkulu - Sastia Hendri Wibowo; Diana Diana (Apik Cahaya Ilmu, 2026)
Digital transformation in the education sector requires educators to master future technological competencies, particularly coding and artificial intelligence. This community service activity aims to improve digital literacy and basic programming skills for teachers in Bengkulu City. The implementation method includes a series of In-Service Training and On-the-Job Training with a total duration of 74 hours of lessons. The training materials cover the concepts of computational thinking, unplugged coding practices, and the use of generative AI tools to support learning. The results of the activity showed a significant increase in participants' understanding of programming logic and their ability to design innovative AI-based teaching media such as interactive quizzes and visual assistants. The final evaluation through peer teaching showed that participants were able to develop creative and child-friendly learning scenarios, which in turn encouraged the creation of a coaching culture between teachers for the sustainability of good practices in schools.